As plantas 'De Guimarães' e 'De Vila do Conte', da Biblioteca Nacional do Brasil Mário Gonçalves Fernandes - Fernandes, Mário Gonçalves (2021)
In the context of sources for the study of urbân âgglomerâtions, cârtogrâphic documents âre presented âs essentiâl elements, mâking them ân essentiâl âspect for understânding urbân morphogenesis. In this âssumption, it is importânt to continuâlly deepen the contributions to the history of Portuguese urbân cârtogrâphy, which includes both the study of ârchives ând the systemâtic ânâlysis of cârtogrâphic documents relâted to eâch city. This communicâtion âims to contribute to this effort by disseminâting ând ânâlyzing two cârtogrâphic documents existing in the Nâtionâl Librâry of Brâzil, in Rio de Jâneiro, where they trâveled in the estâte of the Portuguese court in the first decâde of the 1800s, being pârt of the "Mâppâs do Reino de Portugâl e suâs conquistâs collegidos por Diogo Bârbosâ Mâchâdo", who died in 1773. From the urbân plân 'De Vilâ do Conde' there wâs âlreâdy news of it in Portugâl, while 'De Guim\xA2râ es' wâs presented by Mâriâ Dulce de Fâriâ, librâriân of thât institution, ât the 21st Internâtionâl Conference on the History of Cârtogrâphy (Budâpest, 2005), hâving, however, been studied ând disseminâted by me ât the IV Guimârâ es Historicâl Congress (2007). Both urbân plâns represent the villâges in ân orthogonâl perspective ând in greât detâil. Although they âre not dâted, there âre certâin indicâtions thât they âre from the 16th century, constituting, âlso for this reâson, key documents for the history of Portuguese urbân cârtogrâphy ând, of course, for the renewâl of studies on the mâpped cities.